HAKIKAT ILMU PENGETAHUAN DALAM ISLAM (Analisis Filosofis Dan Implikasinya) - alfaruki, achmad (Al-Iqro', 2024)
Humans are perfect creatures created by Allah SWT. This perfection is in the form of reason and the carrying capacity of the other senses. With this perfection, it is human beings who are tasked with being caliphs on this earth. As caliphs, humans strive to create a civilization of life that continues to develop continuously. To support this civilization, humans need science and knowledge. Science and knowledge emerge with the existence of the human mind, which has been gifted by Allah SWT. This study employs a library-based approach. The results of the research analysis were taken from primary data as the main source, namely a book entitled "Philosophy of Islamic Education Towards Character Building in Facing Global Currents," written by Prof. Dr. H. Maragustam, M.A., and supported by secondary data. The purpose of this research is to find out and understand the nature of knowledge in Islam and what its implications are. The essence of knowledge in Islam is the result of thoughts and the search for truth by humans based on the guidelines of Muslims, namely the Qur'an and the Hadith. Knowledge is something that is believed and can be accepted by reason based on the reality of existence. Knowledge is the result of knowing an object. Science is something that is certain, systematic, scientific, and includes truth based on facts. The implications of science in life are the empowerment of human life, the advancement of science and technology, the development of civilization, spiritual growth and closeness to Allah SWT, as well as maintaining the environment and the earth.